Needs Analysis for Mobile Learning of Plant Structure and Development Topic - Ahya Mujahidin; Murni Sapta Sari; Suhadi Suhadi (Jurnal Pendidikan Sains, 2020)
Abstract: Digital media has the potential to support learning, such as Mobile Learning. The fact show that students currently have not matched their ability to use digital media for the sake of obtaining information. The purpose of this study was to analyze the media learning needs of Plant Structure and Development material. This type of research is descriptive qualitative with observations and surveys. Research instruments in the form of observation sheets and questionnaires. This research was conducted from July to September 2019 at the Biology Education Study Program, FMIPA, UM. The research subjects consisted of 33 students and 1 lecturer. The technique of determining the sample using purposive sampling. The results showed that the subject of Plant Structure and Development requires Mobile Learning media.Abstrak: Media digital berpotensi mendukung pembelajaran, seperti Mobile Learning. Fakta menunjukkan bahwa mahasiswa saat ini belum mengimbangi kemampuannya menggunakan media digital untuk kepentingan memperoleh informasi. Tujuan penelitian ini untuk menganalisis kebutuhan media pembelajaran materi Struktur dan Perkembangan Tumbuhan. Jenis penelitian ini adalah deskriptif kualitatif dengan observasi dan survei. Instrumen penelitian berupa lembar observasi dan kuisioner. Penelitian ini dilakukan bulan Juli sampai September 2019 pada Prodi Sarjana Pendidikan Biologi, FMIPA, UM. Subjek penelitian terdiri dari 33 mahasiswa dan 1 dosen. Teknik penentuan sampel menggunakan purposive sampling. Hasil penelitian menunjukkan bahwa pembelajaran Mata Kuliah Struktur dan Perkembangan Tumbuhan membutuhkan media Mobile Learning.